PENGARUH HARGA DAN LABEL HALAL TERHADAP KEPUTUSAN PEMBELIAN PRODUK KEMASAN IMPOR SAMYANG RAMEN PADA MAHASISWA INSTITUT STIAMI ( STUDI KASUS KAMPUS PUSAT ANGKATAN 2018 ) - Epilia Yudana; Juardi Juardi (JAMBIS : Jurnal Administrasi Bisnis, 2022)
The purpose of this study was to determine (1) the effect of price on purchasing decisions, (2) the effect of halal labels on purchasing decisions, (3) the simultaneous effect of prices and halal labels on purchasing decisions. This research is a quantitative research that emphasizes on testing theories through measuring numerical variables and analyzing data using statistical procedures. The population in this study included 130 people. Based on the results of the study, it can be concluded that price affects purchasing decisions among students of the STIAMI Institute (Central Campus, Class 2018). Thus, if the price is increased, there will be an increase in purchasing decisions among students of the STIAMI Institute (Central Campus, Class 2018). The halal label is also a factor that influences purchasing decisions among STIAMI Institute students (Central Campus, Class 2018). Simultaneously, the variables of Price and Halal Label have an influence on Purchasing Decisions among students of STIAMI Institute (Central Campus, Class 2018).